Lattice Boltzmann Simulation of Coupling Heat Transfer between Solid and Gas Phases of Nanoporous Materials - Yafen Han; Shuai Li; Haidong Liu; Yucong Li (Nanomaterials, 2022)
In order to deeply study the heat conduction of nanoporous aerogel, a model of gas-solid heat conduction was established based on the microstructure of aerogel. The model was divided into two subdomains with uniform mesh because of the different gas-solid characteristics, and simulation was performed on each domain using the lattice Boltzmann method. The value of temperature on the boundaries of subdomains was determined by interpolation. Finally, the temperature distribution and the thermal conductivity were maintained. It can be concluded that when the gas-phase scale was fixed, the temperature distribution of the solid phase became more uniform when the scale increased; when the solid-phase scale was fixed, the temperature jump on the gas-solid interface decreased with the increase in the gas-phase scale; and the thermal conductivity of gas-solid coupling varied with the scale of the gas phase or solid phase, showing a scale effect in varying degrees.